Quantitative methods to assess cerebral haemodynamics - Hall, Emma Louise (2012)
In this thesis methods for the assessment of cerebral haemodynamics using 7 T Magnetic Resonance Imaging (MRI) are described. The measurement of haemodynamic parameters, such as cerebral blood flow (CBF), is an important clinical tool. Arterial Spin Labelling (ASL) is a non-invasive technique for CBF measurement using MRI. ASL methodology for ultra high field (7 T) MRI was developed, including investigation of the optimal readout strategy. Look-Locker 3D-EPI is demonstrated to give large volume coverage improving on previous studies. Applications of methods developed to monitor functional activity, through flow or arterial blood volume, in healthy volunteers and in patients with low grade gliomas using Look-Locker ASL are described. The effect of an increased level of carbon dioxide in the blood (hypercapnia) was studied using ASL and functional MRI; hypercapnia is a potent vasodilator and has a large impact on haemodynamics. These measures were used to estimate the increase in oxygen metabolism associated with a simple motor task. To study the physiology behind the hypercapnic response, magnetoencephalography was used to measure the impact of hypercapnia on neuronal activity. It was shown that hypercapnia induces widespread desynchronisation in a wide frequency range, up to ~ 50 Hz, with peaks in the sensory-motor areas. This suggests that hypercapnia is not iso-metabolic, which is an assumption of calibrated BOLD. A Look-Locker gradient echo sequence is described for the quantitative monitoring of a gadolinium contrast agent uptake through the change in longitudinal relaxation rate. This sequence was used to measure cerebral blood volume in Multiple Sclerosis patients. Further development of the sequence yielded a high resolution anatomical scan with reduced artefacts due to field inhomogeneities associated with ultra high field imaging. This allows whole head images acquired at sub-millimetre resolution in a short scan time, for application in patient studies.